Desenvolvimento de uma formulação cólon específica visando o tratamento da colite ulcerativa - Nagashima Junior, Toshiyuki (2009)
Micro and nanoparticulate systems as drug delivery carriers have achieved successful therapeutic use by enhancing efficacy and reducing toxicity of potent drugs. The improvement of pharmaceutical grade polymers has allowed the development of such therapeutic systems. Microencapsulation is a process in which very thin coatings of inert natural or synthetic polymeric materials are deposited around microsized particles of solids or around droplets. Products thus formed are known as microparticles. Xylan is a natural polymer abundantly found in nature. It is the most common hemicellulose, representing more than 60% of the polysaccharides existing in the cell walls of corn cobs, and is normally degraded by the bacterial enzymes present in the colon of the human body. Therefore, this polymer is an eligible material to produce colon-specific drug carriers. The aim of this study was to evaluate the technological potential of xylan for the development of colon delivery systems for the treatment of inflammatory bowel diseases. First, coacervation was evaluated as a feasible method to produce xylan microcapsules. Afterwards, interfacial cross-linking polymerization was studied as a method to produce microcapsules with hydrophilic core. Additionally, magnetic xylan-coated microcapsules were prepared in order to investigate the ability of producing gastroresistant systems. Besides, the influence of the external phase composition on the production and mean diameter of microcapsules produced by interfacial cross-linking polymerization was investigated. Also, technological properties of xylan were determined in order to predict its possible application in other pharmaceutical dosage forms